Treatment of Fragile X Syndrome with Cannabidiol: A Case Series Study and Brief Review of the Literature - Nicole Tartaglia; Marcel O. Bonn‐Miller; Randi J. Hagerman (2019)
Fragile X syndrome (FXS) is an X-linked dominant disorder caused by a mutation in the fragile X mental retardation 1 gene. Cannabidiol (CBD) is an exogenous phytocannabinoid with therapeutic potential for individuals with anxiety, poor sleep, and cognitive deficits, as well as populations with endocannabinoid deficiencies, such as those who suffer from FXS. The objective of this study was to provide a brief narrative review of recent literature on endocannabinoids and FXS and to present a case series describing three patients with FXS who were treated with oral CBD-enriched (CBD+) solutions. We review recent animal and human studies of endocannabinoids in FXS and present the cases of one child and two adults with FXS who were treated with various oral botanical CBD+ solutions delivering doses of 32.0 to 63.9 mg daily. Multiple experimental and clinical models of FXS combine to highlight the therapeutic potential of CBD for management of FXS. All three patients described in the case series exhibited functional benefit following the use of oral CBD+ solutions, including noticeable reductions in social avoidance and anxiety, as well as improvements in sleep, feeding, motor coordination, language skills, anxiety, and sensory processing. Two of the described patients exhibited a reemergence of a number of FXS symptoms following cessation of CBD+ treatment (e.g., anxiety), which then improved again after reintroduction of CBD+ treatment. Findings highlight the importance of exploring the therapeutic potential of CBD within the context of rigorous clinical trials.